Persons : human and divine - Van Inwagen, Peter; Zimmerman, Dean W (New York Clarendon Press. Oxford, 2007)
The nature of persons is a perennial topic of debate in philosophy. This volume brings together metaphysical debates about the nature of human persons with related debates in philosophy of religion and theology. It explores idealist, dualist, and materialist views of persons
Idealism vindicated / Robert M. Adams -- The self and time / Howard Robinson -- Cartesian dualism / John Hawthorne -- Materialism and Christian belief / Alvin Plantinga -- From mental/physical identity to substance dualism / Richard Swinburne -- Ghosts are chilly / W.D. Hart and Takashi Yagisawa -- Cartesian psychophysics / Hong Yu Wong -- A materialist ontology of the human person / Peter van Inwagen -- I am not an animal! / Hud Hudson -- On the intrinsic value of human persons / Philip L. Quinn -- Persons and the natural order / Lynne Rudder Baker -- The Word made flesh : dualism, physicalism, and the incarnation / Trenton Merricks -- The tree of life : agency and immortality in a metaphysics inspired by quantum theory / Peter Forrest -- The metaphysics of original sin / Michael C. Rea -- Modes without modalism / Brian Leftow
Includes bibliographical references and index
Keywords: Persons; Metaphysics; Philosophical anthropology; Aufsatzsammlung; Aufsatzsammlung